Prostate cancer survivorship: a review of erectile dysfunction and penile rehabilitation after prostate cancer therapy. Issue 10 (2nd June 2014) - Chung, Eric; Gillman, Michael
Summary: Prostate cancer diagnosis and treatment adversely affect quality of life for most men. The true incidence of erectile dysfunction (ED) after prostate cancer therapy is unknown, and the rates of ED in radical prostatectomy (RP) and radiation groups are similar, although the onset of ED is often later in patients treated with radiation therapy. Proposed pathophysiological mechanisms of ED include neurovascular injury, local inflammatory changes, damage to nearby supporting structures, cavernosal smooth muscle hypoxia with ensuing smooth muscle apoptosis and fibrosis, and corporal veno‐occlusive dysfunction causing venous leakage. Penile rehabilitation aims to help men regain the ability to achieve erections sufficient for satisfactory sexual intercourse during rehabilitation from prostate cancer treatment, and ultimately to return to pretreatment erectile function. While there is no consensus on the ideal rehabilitation regimen, many sexual health experts agree that treatment should start as soon as possible to protect and/or prevent corporal endothelial and smooth muscle damage. Current management strategies for erectile function rehabilitation predominantly relate to patients who have had RP. Phosphodiesterase type 5 inhibitors, intracavernosal injection of vasoactive agents and vacuum erection devices are options which can be used in a rehabilitation program. Penile implants should be considered if patients do not respond to medical therapies. To facilitate informed decision making, patients should be presented with all treatment options, and told that rehabilitation and treatment for ED as early as possible after prostate cancer therapy will result in faster and better recovery of erectile function and preserve sexual continuity.